1984
DOI: 10.1136/ard.43.6.810
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis and rheumatic syndromes in Saudi Arabia.

Abstract: SUMMARY Seventy-three episodes of brucellosis in 55 patients are reported. Twenty-two had a systemic illness, 10 arthritis, 10 spondylitis, and four arthritis and spondylitis. Cultures were positive in 77% of cases where appropriate methods were used. A number of rheumatic syndromes may be mimicked by brucellosis and others may coexist with it. A high index of suspicion should prevail in the evaluation of patients from endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…[9][10][11][12][13][14] This surge in incidence of brucellosis in animals and humans during this period has been strongly linked to the uncontrolled importation of potentially infected animals with brucellosis, widespread animal husbandry, and the prevailing habit of ingesting raw milk or its products among the population of nomadic background.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] This surge in incidence of brucellosis in animals and humans during this period has been strongly linked to the uncontrolled importation of potentially infected animals with brucellosis, widespread animal husbandry, and the prevailing habit of ingesting raw milk or its products among the population of nomadic background.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that the brucellosis caused Brucella spp involved a diversity of clinical signs and symptoms including arthritis (31)(32)(33)(34)(35). Furthermore, some studies showed the relationship of brucellosis and rheumatic symptoms (32).…”
Section: Discussionmentioning
confidence: 99%
“…The other clinical features of brucellosis include: night sweats, chills and rigors, anorexia, malaise, weakness, weight loss, headache, arthralgia, myalgia, low backache, dizziness, depressed mood, dyspepsia, nausea, vomiting, abdominal pain, cough, dyspnea, epistaxis and hemoptesis, burning micturition, testicular pain, swollen and tender joints, tenderness over the lumbosacral spine, splenomegaly, hepatomegaly, external lymphadenopathy, jaundice, mouth ulcerations, scrotal swelling in addition to various cutaneous eruptions [1-5,9-11,22,57,-61]. In a study performed in Saudi Arabia that included 73 episodes of brucellosis in 55 patients, 44% of the patients had rheumatic manifestations such as arthritis and spondylitis [62]. Brucellosis can have several presentations and the disease has several stages: acute, sub-acute, chronic, relapsing, active and non-active.…”
Section: Clinical Manifestations Of Brucellosismentioning
confidence: 99%
“…Relapses occur in up to 29% of patients with brucellosis and they usually occur within 12 months of discontinuation of the antimicrobial therapy [1,3,5,58,62]. The risk factors for relapse include: male sex, old age, lymphopenia, deficient immunologic response such as in patients having human immunodeficiency virus (HIV) infection, presence of an aggressive disease or a chronic infection, positive blood cultures during initial infection, and an inadequately treated infection [1,3,5,[83][84][85][86].…”
Section: Relapse Of Brucellosismentioning
confidence: 99%